Evaluation of Student Achievement In Understanding English Language Materials at The Elementary Level In SD 060913: Analysis of Speaking Skills - Arifya, Hany; Sidabutar, Nadin Azzura; Siswanti, Nadila; Sitepu, Nadzwa Hakim (Yayasan Daarul Huda Kruengmane, 2024)
The study aims to evaluate students' achievement in understanding English materials at the primary level through the analysis of speaking skills. The results show that students have poor speaking skills, especially in using the right words and correct sentence structure. Teachers need to increase guidance and supervision of students in speaking so that they can improve their speaking skills. The research method used was qualitative with observation and in-depth interview techniques. This research provides recommendations for curriculum development and more effective teaching strategies to improve students' speaking skills at the primary level. As such, this research makes an important contribution to improving the English speaking skills of primary school students through a more focused and targeted approach, and provides a foundation for the development of better education in the future.